2019
DOI: 10.1097/shk.0000000000001312
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor (HIF)-1α Promotes Inflammation and Injury Following Aspiration-Induced Lung Injury in Mice

Abstract: Acid aspiration-induced lung injury is a common disease in the intensive care unit (ICU) and acute respiratory distress syndrome (ARDS). Hypoxia-inducible factor (HIF)-1α is a major transcription factor responsible for regulating the cellular response to changes in oxygen tension. A clear understanding of the function of HIF-1α in lung inflammatory response is currently lacking. Here, we sought to determine the role of HIF-1α in type 2 alveolar epithelial cells (AEC) in the generation of the acute inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…HIF‐1α was not strongly expressed in the injured groups (HCl‐ZEEP), suggesting that tissue hypoxia did not mediate neutrophil activation and migration and that elevated lactate‐to‐pyruvate ratio was primarily the result of inflammation. Our observation is consistent with another study of aspiration pneumonitis in a murine model showing mild HIF‐1α elevation 5 hours after acid instillation 34 . Therefore, it is likely that we did observe an increase in HIF‐1α, as our study ended 4 hours after acid instillation.…”
Section: Discussionsupporting
confidence: 92%
“…HIF‐1α was not strongly expressed in the injured groups (HCl‐ZEEP), suggesting that tissue hypoxia did not mediate neutrophil activation and migration and that elevated lactate‐to‐pyruvate ratio was primarily the result of inflammation. Our observation is consistent with another study of aspiration pneumonitis in a murine model showing mild HIF‐1α elevation 5 hours after acid instillation 34 . Therefore, it is likely that we did observe an increase in HIF‐1α, as our study ended 4 hours after acid instillation.…”
Section: Discussionsupporting
confidence: 92%
“…HIF-2α upon activation increases the expression of vascular-endothelial protein thyrosine phosphatase, which in turn decreases VEcaderin phosphorylation, supporting the integrity of adherens junctions and preventing loss of endothelial barrier function [64]. Contrarily, expression of HIF-1α in alveolar epithelial cells enhances lung inflammation in a NF-kB mediated way [65] and favors a cell-mediated inflammation (CD4+ CD8+) and proinflammatory cytokines (IL-2 and TNFα), which proportionately downregulate CD55 and augment complement-mediated endothelial damage [8]. Moreover, myeloid cell HIF-1α is a key driver of myeloid cell response in hypoxic and inflammatory microenvironments by modulating cellular energetics, upregulating glycolytic enzymes and glucose transporters to permit ATP generation under conditions of hypoxia, and preventing apoptosis of innate immunity cells.…”
Section: Hypoxia-mediated Endothelial Damagementioning
confidence: 99%
“…A close link exists between hypoxia and inflammation [ 73 ]. Previous works have reported that different organs in the hypoxic environment exhibit different responses at the transcriptional, translational, and post-translational levels [ 77 , 78 ]. HIF-1α, a pivotal transcription factor in hypoxic induction, activates iNOS gene expression, contributing to increased NO synthesis.…”
Section: Inflammation In Osasmentioning
confidence: 99%